Near infrared photoimmunotherapy targeting the cutaneous lymphocyte antigen for mycosis fungoides. (3rd July 2021) - Silic-Benussi, Micol; Saponeri, Andrea; Michelotto, Anna; Russo, Irene; Colombo, Anna; Pelizzo, Maria Guglielmina; Ciminale, Vincenzo; Alaibac, Mauro
ABSTRACT: Background : Mycosis fungoides (MF) is a low-grade T-cell lymphoma with primary cutaneous involvement accounting for more than half of all primary cutaneous lymphomas. The treatment of MF is very challenging due to the limited therapies available. Near‐infrared photoimmunotherapy (NIR-PIT) is a newly developed and highly selective cancer treatment that employs a monoclonal antibody conjugated to a photo-absorber dye, the hydrophilic phthalocyanine IRdye 700DX® (IR700), and near infrared light. In this study, we investigated the effect of NIR-PIT on MF targeting the cell-surface antigen cutaneous lymphocyte antigen (CLA) Matherial and methods : MF derived My-La CD4+ cells were incubated with the anti-CLA antibody conjugated to IR700 and then irradiated with a 690 nm near-infrared light. Cell death was evaluated by propidium iodide staining and flow cytometry 24 hours after irradiation. Results : Treatment with anti-CLA or light irradiation exhibited very modest pro-death effects, whereas treatment with the anti-CLA antibody conjugated to IR700 and then irradiation with a 690 nm near-infrared light induced a substantial increase in death in the MF cell line. Conclusions : NIR-PIT targeting CLA to treat MF showed marked antitumour effects. As such, CLA-targeted NIR-PIT could be a promising treatment for MF and, possibly, other cutaneous diseases characterized by CLA+ skin infiltrating T-cells.